Compatibility of the biocontrol agent Trichoderma harzianum C52 with selected fungicides - McLean, K.L.; Hunt, J.; Stewart, A. (New Zealand Plant Protection, 2001)
Trichoderma harzianum C52 is an effective biocontrol agent of the onion white rot pathogen Sclerotium cepivorum For this biocontrol agent to be integrated into an existing disease management programme it must be compatible with the fungicides commonly used on onions The sensitivity of T harzianum spores to the field rate of eight fungicides commonly applied to onions was determined in an in vitro assay Results indicate that T harzianum was least sensitive to procymidone and captan and most sensitive to mancozeb tebuconazole and thiram A glasshouse pot trial confirmed that T harzianum was sensitive to mancozeb but tolerant of captan This research indicates that in furrow applications of T harzianum would be compatible with a captan and/or benomyl seed treatment for control of other seedling diseases